Penentuan Harga pada Jaringan Interkoneksi Telekomunikasi: Sebuah Studi Pustaka - Eko Atmadji (Sinergi: Kajian Bisnis dan Manajemen, 2012)
The one which influences the price of telecommunication services is interconnection fee. In accordance with interconnection fee, the price determination depends on the types of competition. In symmetric competition and linear pricing, the price would be high because of the penchant of collusion and interconnection fee should be high. The opposite results occur when non linear pricing (two part tariff) is applied because all companies set the interconnection fee close to marginal cost. In asymmetric competition, the price tends to be low. However, the lowness of price caused by the application of predatory pricing by incumbent company and interconnection fee equals with marginal cost. After the entrants were expelled, the price will be higher. The government regulation toward interconnection fee could not be determined because it depends on the types of competition and the pricing linearity.Keywords: telecommunication, interconnection fee, competition, two part tariff